Chemical constituents from Munronia sinica and their bioactivities - Li, Xiao-Li (Springer Berlin Heidelberg, 2012)
Two new minor constituents, musinisins A (1) and B (2), together with five known compounds (3–7), were isolated from the aerial parts of Munronia sinica. Their structures were established by means of spectroscopic methods and the absolute stereochemistry of 1 was determined by single crystal X-ray experiment. Compound 4 showed antiangiogenic activity evaluated by a zebrafish model and apoptosis-inducing effect on A549 lung cancer cells. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-012-0001-8 and is accessible for authorized users.